Genetic improvement of tocotrienol content enhances the oxidative stability of canola oil - Deng, Min; Chen, Hao; Zhang, Wei; Cahoon, Edgar B.; Zhou, Yongming; Zhang, Chunyu (Frontiers in Plant Science, 2023)
Tocotrienols and tocopherols, which are synthesized in plastids of plant cells with similar functionalities, comprise vitamin E to serve as a potent lipid soluble antioxidant in plants. The synthesis tocopherols involves the condensation of homogentisic acid (HGA) and phytyl diphosphate (PDP) under the catalysis of homogentisate phytyltransferase (HPT). Tocotrienol synthesis is initiated by the condensation of HGA and geranylgeranyl diphosphate (GGDP) mediated by homogentisate geranylgeranyl transferase (HGGT). As one of the most important oil crops, canola seed is regarded as an ideal plant to efficiently improve the production of vitamin E tocochromanols through genetic engineering approaches. However, only a modest increase in tocopherol content has been achieved in canola seed to date. In this study, we transformed barley HGGT (HvHGGT) into canola to improve total tocochromanol content in canola seeds. The results showed that the total tocochromanol content in the transgenic canola seeds could be maximally increased by four folds relative to that in wild type canola seeds. Notably, no negative impact on important agronomic traits was observed in transgenic canola plants, indicating great application potential of the HvHGGT gene in enhancing tocochromanol content in canola in the future. Moreover, the oil extracted from the transgenic canola seeds exhibited significantly enhanced oxidative stability under high temperature in addition to the increase in total tocochromanol content, demonstrating multiple desirable properties of HvHGGT.